Isolation and identification of salt-tolerant plant-growth-promoting rhizobacteria and their application for rice cultivation under salt stress - Sultana, Shahnaz; Paul, Sumonta C.; Parveen, Samia; Alam, Saiful; Rahman, Naziza; Jannat, Bushra; Hoque, Sirajul; Rahman, Mohammad Tariqur; Karim, Muhammad Manjurul (Canadian Science Publishing (NRC Research Press), 2020)
Growth and productivity of rice are negatively affected by soil salinity. However, some salt-tolerant rhizosphere-inhabiting bacteria can improve salt resistance of plants, thereby augmenting plant growth and production. Here, we isolated a total of 53 plant-growth-promoting rhizobacteria (PGPR) from saline and nonsaline areas in Bangladesh where electrical conductivity was measured as >7.45 and <1.80 dS/m, respectively. Bacteria isolated from saline areas were able to grow in a salt concentration of up to 2.60 mol/L, contrary to the isolates collected from non-saline areas that did not survive beyond 854 mmol/L. Among the salt-tolerant isolates, Bacillus aryabhattai, Achromobacter denitrificans, and Ochrobactrum intermedium, identified by comparing respective sequences of 16S rRNA using the NCBI GenBank, exhibited a higher amount of atmospheric nitrogen fixation, phosphate solubilization, and indoleacetic acid production at 200 mmol/L salt stress. Salt-tolerant isolates exhibited greater resistance to heavy metals and antibiotics, which could be due to the production of an exopolysaccharide layer outside the cell surface. Oryza sativa L. fertilized with B. aryabhattai MS3 and grown under 200 mmol/L salt stress was found to be favoured by enhanced expression of a set of at least four salt-responsive plant genes: BZ8, SOS1, GIG, and NHX1. Fertilization of rice with osmoprotectant-producing PGPR, therefore, could be a climate-change-preparedness strategy for coastal agriculture.